2022
DOI: 10.1017/s0003055422000326
|View full text |Cite
|
Sign up to set email alerts
|

Social Groups as the Source of Political Belief Systems: Fresh Evidence on an Old Theory

Abstract: We present novel evidence that attitudes toward nonpartisan social groups structure political belief systems. First, we show that most Americans have a rich knowledge of the social groups that support and oppose group-related policies. This knowledge often exceeds people’s awareness of where Democrats and Republicans stand on these same issues. Then, we show that this knowledge promotes what Philip Converse called ideological coherence: Americans who know which groups support and oppose a policy are more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Nor do we assert that the most ideologically sophisticated individuals ought to share the same understandings of these terms. While the textbook definitions are generally consistent with the conventional understanding of ideology in American politics (e.g., Conover and Feldman, 1981;Ellis and Stimson, 2012), political psychology (e.g., Luttbeg and Gant, 1985;Jost et al, 2003;Alford et al, 2005;Jost et al, 2009;Kinder and Kalmoe, 2017;Kalmoe, 2020;Jost, 2021;van der Linden et al, 2021;Elder and O'Brian, 2022), and other major textbooks in American politics (e.g., Ginsberg et al, 2019;Harrison et al, 2019), some may define "liberal" and "conservative" in other ways. Some scholars, for example, have identified a social dimension in which conservatives prefer government intervention more than liberals do (e.g., Layman and Carsey, 2002;Lee, 2009).…”
Section: Three Measures Of Political Ideologymentioning
confidence: 64%
“…Nor do we assert that the most ideologically sophisticated individuals ought to share the same understandings of these terms. While the textbook definitions are generally consistent with the conventional understanding of ideology in American politics (e.g., Conover and Feldman, 1981;Ellis and Stimson, 2012), political psychology (e.g., Luttbeg and Gant, 1985;Jost et al, 2003;Alford et al, 2005;Jost et al, 2009;Kinder and Kalmoe, 2017;Kalmoe, 2020;Jost, 2021;van der Linden et al, 2021;Elder and O'Brian, 2022), and other major textbooks in American politics (e.g., Ginsberg et al, 2019;Harrison et al, 2019), some may define "liberal" and "conservative" in other ways. Some scholars, for example, have identified a social dimension in which conservatives prefer government intervention more than liberals do (e.g., Layman and Carsey, 2002;Lee, 2009).…”
Section: Three Measures Of Political Ideologymentioning
confidence: 64%
“…We focused on attitudes about political policies; however, another type of attitude that is likely relevant in belief systems are people's attitudes about groups. Some recent research suggests that group prejudices, for example, are an important determinant of an attitude's stability (Elder & O'Brian, 2022). Thus, it might be that particular types of attitudes—like values, identities and group prejudices—may be necessary for inter‐attitude centrality effects to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Social sorting occurs when individuals perceive certain social groups as associated with particular political affiliations (Kane et al, 2020; Mason & Wronski, 2018). This research has demonstrated that individuals in the US context pay attention to which social groups support which party and policy positions (Elder & O'Brian, 2022; Mason & Wronski, 2018). Consequently, these perceptions of social sorting influence the degree of affective partisan polarization and shape individuals’ positions on policy issues (Mason & Wronski, 2018).…”
Section: The Development Of Political Identities In the Socio-structu...mentioning
confidence: 99%